UTAK-ATIK KATA PADA PENAMAAN TOKOH DALAM NOVEL NEGERI PEREMPUAN KARYA WISRAN HADI - Armini Arbain (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2018)
Language is upstream for the literary work. In literature, language is not only a means of communication but also a means to express aestethic. To maintain the aestethic, theauthorusing several form connotative, emotive, and aesthetic language. A famous author in West Sumatra, Wisran Hadi, in his novel entitled Negeri Perempuan expresses language creativity in naming the characters. The the method used is qualitative method. The results show each name of the character in the novel has themeaningwhich related to the character it represents. Moreover, it also associated with the background of the work of the cultural background of Minangkabau culture. This research aims to discusslanguage creativity and social conditions of Minangkabau culture represent in the novel.